Mode of Entry and Expropriation - Ramin Dadasov; Jens Oliver Lorz (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
We develop a politico-economic model to analyze the relationship between mode of entry into a new market and institutional quality of the host country. A foreign investor can either purchase a domestic firm, what we consider as FDI, or form a joint venture, in which the control right over the firm rests with the domestic entrepreneur. In an autocratic regime, the ruling elite uses its political power to implement expropriatory policies. In an integrated firm the risk of expropriation targets the foreign investor whereas in a joint venture the domestic agent bears this risk. We determine the equilibrium level of the probability of expropriation and show that the ruling elite, by choosing it, discriminates in favor of the foreign investor. This has implications for the form of invested capital, and thus for the organizational structure of active firms in the host country.
Keywords: F21; L22; P48; 330; Foreign direct investments; joint ventures; property rights; expropriation